Prediction of Toddlers Acute Respiratory Infection (ARI) to Become Pneumonia in Martapura Catchment Area, Banjar District, Indonesia - Leka Lutpiatina MSi; Lilis Sulistyorini MKes; Ririh Yudhastuti Prof; Hari Basuki Notobroto MKes (Global Pediatric Health, 2024)
Introduction. The pneumonia pattern in young children may vary across different catchment areas. Therefore, this study aims to analyze the predictive factors for toddlers with an Acute Respiratory Infection (ARI) developing into pneumonia in the catchment area of Banjar Regency, Indonesia. Methods. A case-control design, with 300 respondents, consisting of 106 cases and 194 controls. A questionnaire of interviews with mothers/caregivers of toddlers. Forty-one indicators data were analyzed using multiple logistic regression with backward stepwise regression to arrive at the final model. Results. The predictive factors for toddlers with pneumonia were the child’s age ( P -value .070), child development ( P -value .007), breastfeeding ( P -value .051), family income ( P -value .026), and location of houses along the river ( P -value .025). Conclusion. A prediction index for toddler pneumonia has been compiled, which can be applied to improve the health of lower middle-class toddlers requiring more government attention.